Readiness assessment for a community-based archiving initiative in Barangay Borol 1st, Balagtas Bulacan - De Jesus, James Kevin R.; Olgado, Benedict S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
Records and archives have always been important to human society. Today, records and archives are not only kept for their evidentiary value, but also for their cultural and historical value. The role of archives in the shaping and reconstruction of "memory"is now recognized. Along with the changing roles of archives, the view of archival institutions as neutral repositories has changed as well given the power exercised in the creation, management and control of archives. As such, how society remembers the past is controlled through archives. Consequently, there are always people and stories that will be excluded, ignored, or represented wrongly in mainstream archives.
Community archiving, an emerging paradigm in the archival field aims to address this problem of exclusion. Through community-based archiving initiatives, the challenge for archives to be more democratic, inclusive, and holistic, listening much more to the citizens than the state is addressed. Community archives empower communities by giving them an avenue for them to care for their own history and memory.
The Philippines has legislative measures with regards to history and memory making but it is not enough to preserve the diversity of the country's heritage. The community archiving approach is then proposed as means for local communities to protect their histories. In line with this, community readiness must first be assessed before a comunity-based archiving initiative is put in place as to produce the desired sustainable effect.
The study adopted the Community Readiness Model (CRM) and the five key principles of community archives observed by Caswell (2014) in assessing the community readiness of Barngay Borol 1st, Balagtas, Bulacan for a community-based archiving initiative. Key respondents from the barangay community were interviewed and analysis was done in order to assess community readiness as well as determine the existence of the key principles of community archives.
The results show that Barangay Borol 1st was still in the Preparation stage, as seen through the Community Readiness Model. The current efforts regarding archiving in the community are mainly record keeping practices. The barangay administration sub-community was identified as the strongest sector in terms of possible support for future initiatives. Lastly, two major themes that greatly affect community readiness and the principles of community archives were discovered. the first was that among the barangay community members, the issue of the need to preserve local history and memory was seen as a concern but not a priority. The second is the need to get the importance of the issue across to the community. The study recommend increasing the awareness and knowledge of the community members outside the leadership concerning the importance of archives. Finding concrete examples situated in the community so that members are able to acquire a sense of connection and responsibility for their records us also important.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Archives -- Philippines -- Bulacan -- Evaluation